Gambaran Motivasi Kepatuhan Radiografer Terhadap Penggunaan Alat Monitoring Dosis Radiasi Personal Thermoluminicence Dosimeter Di Instalasi Radiologi Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Finzia, Pocut Zairiana; Fahrul Roji (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
This study aims to determine the motivation for radiographers' compliance with the personal radiation dose monitoring tool Thermoluminescence Dosimeter at the Radiology Installation of Pertamedika Ummi Rosnati Hospital Banda Aceh. This research is a descriptive study with an observational or non-experimental design with a cross-sectional design and a survey approach with 4 radiographers as respondents to determine the level of motivation for radiographers' compliance and the factors that influence the motivation of radiographers' compliance with the personal thermoluminescence dosimeter radiation dose monitoring tool. Data analysis was carried out univariately. The results of this study indicate that there is motivation for radiographers' compliance with the use of personal thermoluminescence dosimeter radiation dose monitoring tools, namely 75%. and the rest were not motivated by compliance with the use of a personal thermoluminescence dosimeter radiation dose monitoring device, namely 25%, with the characteristics of the respondents being mostly female, 50%. and the remaining 50% are male, and the majority of respondents with an average age of 25-35 is 75%. and the remaining 25% with respondents aged 35-45